Studies in law, politics, and society. Vol. 55 - Sarat, Austin (Bingley, U.K. : Emerald, 2011)
This volume Studies in Law, Politics and Society contains a symposium on indigenous peoples in Latin America. It examines the ways rights are negotiated between those groups and the states in which they live. The articles in the symposium show the different ways the complex politics of rights play out in Latin American nations. They ask us to consider the way context is reflected in the political and legal life of indigenous peoples, and they consider various theoretical paradigms for understanding rights.
Introduction / Kathleen M. Sullivan, Sandra Brunnegger -- Indigenous peoples in Chile : the quest to become a constitutional entity / Jorge Contesse -- Building Mayan authority and autonomy : the'recovery' of indigenous law in post-peace Guatelmala / Rachel Sieder -- Legal imaginaries : recognizing indigenous law in Colombia / Sandra Brunnegger -- Reorganizing indigenous-state relations in Chile : Programa Orenes and participatory governance / Kathleen M. Sullivan -- Racial spectacles : promoting a colorblind agenda through direct democracy / Angelique M. Davis, Rose Ernst -- Norberto Bobbio (1909-2004) and law : a centennial tribute / Teresa Chataway.
Keywords: Sociological jurisprudence; Law -- Political aspects